Production of carbon nanotubes (CNTs) from thermochemical conversion of waste plastics using Ni/anodic aluminum oxide (AAO) template catalyst. (December 2017) - Liu, Xiaotong; Shen, Boxiong; Yuan, Peng; Patel, Dipesh; Wu, Chunfei
Abstract: In this work, the production of carbon nanotubes (CNTs) from waste plastics was investigated to reduce the cost of CNTs production, as well as providing alternative management for waste plastics. A template-based catalyst (Ni/anodic anodic aluminium oxide–AAO) was studied herein to control the growth of CNTs with uniform distribution of diameters. The addition of a conditioning catalyst (for modifying carbon sources) was studied for their influences on the formation of CNTs on Ni/AAO. A two-stage reactor was used to test the prepared catalysts which were also characterized with various methods e.g. scanning electronic microscopy (SEM) and temperature programmed oxidation (TPO). The results show that the introduction of a conditioning catalyst (Ni/Al2 O3 ) positively affected the growth of CNTs with more uniform distribution of diameters of CNTs.